PERLINDUNGAN HUKUM TERHADAP HAK ANAK SEBAGAI PELAKU TINDAK PIDANA PENCURIAN YANG MENGGUNAKAN SENJATA TAJAM PADA TAHAP PENYIDIKAN DI POLRESTA PADANG - Mufty, Mufty; Gusman, Erry; Zulfiko, Riki (UNES Law Review, 2023)
Laws are rules that allow people in general to actively carry out through special intermediaries who have the authority to carry out legal coercion, economic sanctions such as fines, etc. Children are part of the younger generation as one of the human resources who are potential and successors to the ideals of the nation's struggle in the future, who have a strategic role and have special characteristics and characteristics, require guidance and protection in order to ensure balanced physical, mental and social growth and development. Theft with violence from a legal perspective is one of the criminal acts that is troubling and detrimental to society. Therefore, legal action must be taken. The act of motorbike robbery carried out by a group of people or organized is in essence an act that is contrary to religious, moral, ethical and legal norms, and endangers the livelihoods and lives of the community, nation and state. Based on the Criminal Code, begal is included in "Criminal Acts of Theft Chapter XXII specifically regulated in Article 365 of the Criminal Code. This has been regulated in the Criminal Code Article 365 paragraphs (1), (2) and (3), namely with a maximum penalty of nine years, twelve years, even life imprisonment. The type of research used is Juridical Empirical. The research results obtained, namely: 1). Legal protection for minors who commit criminal acts of theft using sharp weapons in the jurisdiction of the Padang Polrestabes. 2). Obstacles and efforts faced by Padang Police investigators in protecting children's rights as perpetrators of crimes of theft using sharp weapons in the jurisdiction of the Padang Polrestabes. Based on the results of the research it is suggested: The members of the Padang Polrestabes are more active and effective in conducting outreach to the public regarding the large number of crimes or criminal acts of theft that use sharp weapons